Analysis of Liquidity Ratios and Profitability Ratios to Assess Financial Performance at PT. Unilever Indonesia Tbk for the Years 2015–2024 - masni, Masni; Eko Giyatiningrum, Eko Giyatiningrum (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the financial performance of PT Unilever Indonesia Tbk during the 2015-2024 period based on liquidity and profitability ratios. The research employs a descriptive quantitative method using secondary data obtained from the company’s annual financial statements. The analysis is conducted through the calculation of the Current Ratio (CR) and Quick Ratio (QR) as liquidity indicators, as well as the Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Investment (ROI), and Return on Equity (ROE) as profitability indicators. The results show that both liquidity and profitability ratios experienced fluctuations with a downward trend, particularly since 2019, due to declining sales and increasing operating expenses. Overall, the company’s financial performance is considered fairly good but shows a decreasing trend. It is recommended that the company improve asset management efficiency, cost control, and sales strategies to enhance liquidity and profitability in the future.